SEBARAN LOKASI DAN KARAKTERISTIK MODAL INDUSTI KECIL RUMAH TANGGA DI KECAMATAN SUSUKAN KABUPATEN SEMARANG - Shohibbudin, Shohibbudin; Hardati, Puji; Putro, Saptono (Geo-Image, 2017)
This research aims to describe: 1) the distribution of small home industries including the location of the industries, the source of raw materials, and the range of industries’ marketing, 2) the characteristic of small home industries capital, 3) the labor absorption rate, 4) the contribution of the income of the small home industries to the family income.The research method is survey, documentation, and interview. The research result is the spatial distribution of the small home industries is in the entire village in Susukan District. The labors absorption in Susukan District is 5%. The average incomes of the small home industries is Rp 4.200.000,- per month. The contribution of the income of the small home industries to the family income is 75%.